Research on System Dynamics Simulation for NIMBY Risk Diffusion of the ‘One Belt and One Road’ Energy Investment - Jian Hu, Junyi Li, Dong Pu, Jinhua Sun (Forest Chemicals Review)
Under the background of China’s ‘one belt and one way’ energy cooperation, overseas energy investment has been increasing, but at the same time, there is also a serious problem on Not In My Back Yard risk. How to reduce the loss brought by the diffusion of NIMBY risk to the overseas energy investment of Chinese enterprises, it is the key to deeply explore the main diffusion mechanism of this risk formation. Based on this, on the basis of making in-depth analysis of the main factors affecting the NIMBY risk diffusion of energy investment, this paper constructs an analysis model on the NIMBY risk diffusion mechanism with system dynamics, and combines with an example, uses Vensim-PLE software to simulate and analyze the sensitivity. The results show that the related stakeholder behaviors, including the information openness of construction enterprises, the credibility of the host government and the satisfaction of the host residents, have positive effects on alleviating the diffusion of NIMBY risk of energy investment. Based on the change of the function rules among the elements by the simulation results, from the perspective of improving the benefit compensation mechanism and communication mechanism of NIMBY risk of energy foreign investment, the satisfaction of the host residents can be improved by promoting the credibility of the host government and the information openness of the construction enterprises, and then the probability of the NIMBY risk diffusion can also be reduced.